Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1097/00006454-199812000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of rotavirus diarrhea in children with immunoglobulin from immunized bovine colostrum

Abstract: Treatment with antirotavirus immunoglobulin of bovine colostral origin is effective in the management of children with acute rotavirus diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 26 publications
1
97
0
2
Order By: Relevance
“…8,9 Our study shows that recovery time and length of hospital stay were shorther in the treatment group. Similar results were reported by Ylitalo et al 8 12 in Bangladesh in which oral hyperimune bovine colostrum was effective to accelerate the recovery time and the length of hospital stay for acute diarrhea caused by rotavirus in infants and children compared with control of 56 hours compared to 72 hours.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…8,9 Our study shows that recovery time and length of hospital stay were shorther in the treatment group. Similar results were reported by Ylitalo et al 8 12 in Bangladesh in which oral hyperimune bovine colostrum was effective to accelerate the recovery time and the length of hospital stay for acute diarrhea caused by rotavirus in infants and children compared with control of 56 hours compared to 72 hours.…”
Section: Discussionmentioning
confidence: 62%
“…Bovine colostrums also contain growth factors that are synergically useful for the diarrhea recovery. [8][9][10] This study aimed to evaluate the role of bovine colostrums to the recovery time and the length of hospital stay in infants and children who suffered from acute diarrhea.…”
mentioning
confidence: 99%
“…α-LA and β-LG were present as major components in F3. As mentioned above, IgG was identified as a rotavirus inhibitor in bovine milk (Ebina et al, 1992;Sarker et al, 1998). Accordingly, to address the contribution of IgG to the anti-HRV activity of Dried MFRF, we attempted to separate IgG in each fraction from other components by using affinity chromatography on a HiTrap Protein G HP column (5 ml, GE Healthcare UK Ltd.).…”
Section: Analysis Of the Protective Components In Dried Mfrfmentioning
confidence: 99%
“…It has been proposed that passive protection against HRV infection could be achieved by using immunoglobulin G (IgG) from the colostrum of cows hyper-immunized with rotavirus (Ebina et al, 1992;Sarker et al, 1998). Unfortunately, the clinical use of bovine colostrum from hyper-immunized cows has been limited because of difficulties in largescale production.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the oral rehydration solution (ORS) recommen ded by World Health Organization (WHO) [10,11] , reduced osmolarity ORS [8] , addition of Lactobacillus GG to ORS [12,13] , and rice-based solution [14] have been used to treat this disease. Also, oral immunoglobulins was used as antiviral therapy [15,16] , and rotavirus candidate vaccines are developing [17] , in which a oral tetravalant, rhesus rotavirus-based, human reassortant vaccine has been licensed in USA [18] . To seek more effective and cheaper drugs to treat rotaviral diarrhea from Chinese medicinal herbs, we found that a Chinese traditional medical prescription named Qiwei Baizhu Powder (QWBZP) had been employed to treat acute diarrhea in infants and children for nearly one thousand years in Traditional Chinese Medicine (TCM).…”
Section: Introductionmentioning
confidence: 99%